2017
DOI: 10.1038/srep40892
|View full text |Cite
|
Sign up to set email alerts
|

A single identified glomerulus in the zebrafish olfactory bulb carries the high-affinity response to death-associated odor cadaverine

Abstract: The death-associated odor cadaverine, generated by bacteria-mediated decarboxylation of lysine, has been described as the principal activator of a particular olfactory receptor in zebrafish, TAAR13c. Low concentrations of cadaverine activated mainly TAAR13c-expressing olfactory sensory neurons, suggesting TAAR13c as an important element of the neuronal processing pathway linking cadaverine stimulation to a strongly aversive innate behavioral response. Here, we characterized the initial steps of this neuronal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 38 publications
(68 reference statements)
2
32
0
Order By: Relevance
“…Gαolf is a mature ORN marker and that in zebrafish it allowed the recognition of the dendrite knobs of cORNs (Dieris et al, 2017), Gαolf antiserum was useful to identify cORNs in A. anisitsi. In addition, the ir-OMP ORNs exhibited the same morphology and location as cORNs identified by the histological study, similar to that observed in D. rerio (Sato et al, 2007) and…”
Section: Discussionmentioning
confidence: 99%
“…Gαolf is a mature ORN marker and that in zebrafish it allowed the recognition of the dendrite knobs of cORNs (Dieris et al, 2017), Gαolf antiserum was useful to identify cORNs in A. anisitsi. In addition, the ir-OMP ORNs exhibited the same morphology and location as cORNs identified by the histological study, similar to that observed in D. rerio (Sato et al, 2007) and…”
Section: Discussionmentioning
confidence: 99%
“…TrkA-Dependent Manner. Studies in fish have demonstrated that pERK staining and c-fos gene expression are suitable markers of neuronal activation upon odorant exposure in the OO and CNS (23,24). However, whether viruses activate neurons in the OO and OB has not been investigated.…”
Section: Neurotropic Viruses Activate Sensory Neurons In the Oo And Omentioning
confidence: 99%
“…Trace Amines and Their Receptors project to dorsolateral glomeruli of the olfactory bulb, evoking innate avoidance behavior (Hussain et al, 2013;Dieris et al, 2017). Structure-activity analysis indicated that TAAR13c has a preference for medium-sized diamines containing an odd number of carbons and contains a nonclassic monoamine recognition pocket with two distinct cation recognition sites (Hussain et al, 2013).…”
Section: Teleost Olfactory Responsesmentioning
confidence: 99%
“…Neurons expressing a functional TAAR do not express other TAARs or olfactory receptors, whereas neurons expressing a TAAR pseudogene may express a second TAAR (Liberles and Buck, 2006;Johnson et al, 2012;Pacifico et al, 2012). Expressed TAAR proteins are found in the olfactory cilia, the site of odor detection, and axons project to distinct glomeruli within the dorsomedial domain of the olfactory bulb (Pacifico et al, 2012;Dieris et al, 2017), although this may be developmentally regulated in some species (Gliem et al, 2009;Shao et al, 2017). Like classic olfactory receptor neurons, TAAR neurons express G olf and related signaling proteins, and inhibition of adenylyl cyclase blocks the odor-related responses of TAAR neurons (Liberles and Buck, 2006;Ferrero et al, 2012;Zhang et al, 2013).…”
Section: E Trace Amine-associated Receptors In Olfactionmentioning
confidence: 99%